Market Development Strategy for Building Management Business Through the Integration of PESTEL, SWOT-TOWS, and ISM Frameworks - Muhammad Ali Murtadha; Daman Sudarman (Amkop Management Accounting Review (AMAR), 2026)
The Building Management industry in Jakarta faces challenges from economic volatility and post-pandemic shifts in workspace preferences. PT XYZ, a national private company, experienced significant fluctuations in revenue growth, reaching a contraction of -7.7% in 2024. This condition requires PT XYZ to expand its market, which is currently concentrated within a captive market. This study aims to formulate alternative concepts for a comprehensive market expansion strategy using a multi-framework approach. The research method employed is descriptive qualitative with a case study approach. The analysis was conducted by identifying macro factors (PESTEL) combined with internal capability analysis (SWOT) and strategy synthesis (TOWS), as well as hierarchical modeling using Interpretative Structural Modelling (ISM) powered by Exsimpro ISM software. The results map PT XYZ's alternative market expansion strategies into a seven-level hierarchical structure divided into three implementation phases. The internal consolidation and capability foundation (enabler) phase at Levels 7 and 6 relies on digitalization, human resource up-skilling programs aligned with ESG trends, capitalization of Greenship expertise and Quality Management Systems, and the formation of an agile organization. The intermediate phase at Levels 5 and 4 serves as acceleration through the strengthening of Business Development functions, B2B digital marketing, and leveraging affiliate credibility alongside financial liquidity governance resilience. The peak phase (Levels 3, 2, and 1) represents the final output in the form of a cost leadership strategy with service differentiation and strategic alliances to execute market expansion into non-CBD segments, government infrastructure, and State-Owned Enterprises.